Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPA Melalui Metode Demonstrasi Di Kelas IV SD Inpres VII Labuan Baru - Kurniati, Yuli (Jurnal Kreatif Online, 2014)
The main problem of this research was that can demonstration method increase the students’ learning outcome especially in natural science to the fourth grade students of SD Inp.7 Labuan Baru. The objective of this classroom action research was to increase the students’ learning outcome in science through demonstration method. The subject of this research was 23 students of the fourth grade consisting of 12 boys and 11 girls. The instrument of data collection was achievment test. The design of this research was conducted in two cycles and each cycle has four stages : (1) planning, (II) action, (III) observation, (IV) reflection. Cycle I shows that the students’ activity was sufficient while in cycle two increased to very good. Scoring in cycle I was categorized as good and increased to good and very good in cycle II. Demonstration method is effective enough to maximize the students’ learning outcome in order to be better and achievable. Observation result in cycle I and II shows the students and teachers were increased or categorized very well in learning activity. Based on the analysis of students’ learning outcome in cycle I, 14 out of 23 students reached the minimum criteria of test with 60.87% of classical mastery, and 70.35% of classical achievement whereas in cycle II out of 23 students reached the minimum criteria of test, classical mastery 95.65% and classical achievement 81.56%. It shows that there was an increase from cycle I to cycle II between the classical achievement and individual mastery. Therefore, it can be concluded that the use of demonstration method can increase the students’ learning outcome particularly in natural science to the fourth grade students of SD Inp.7 Labuan Baru. Keywords: Students’ Learning Outcome, Demonstration Method.